Natural Spawning Technique of Seahorse (Hippocampus comes) In Center For Marine Cultivation Fisheries of Lampung - Lusiana BR Ritonga (Universitas Tidar, 2022)
Seahorse (Hippocampus comes) is a fishery commodity that has high economic value, both alive and dead. Seahorse seeds production was highly dependent on the availability of large and high quality gonad mature stock. One alternative that can be done to meet the needs of seeds by naturally spawning. The main parameters observed in this study were egg incubation, harvesting of juveniles, maintenance of juveniles, growth and survival of juveniles and maintenance of seeds. The water quality during the observation was still in the normal range, the temperature ranges between 29,6 0C, pH between 7,71-7,96 and dissolved oxygen between > 4,90-5,22 mg / l.